A complete guide to Docker for operations and development : test-prep for the Docker Certified Associate (DCA) exam - Fouda, Engy (Apress, 2022)
Harness the power of Docker by containerizing your code with all its libraries and file systems to consistently run anywhere. This book is your source for learning all about Docker operations and development. Its divided into two units and focuses on the topics that the Docker Certified Associate exam covers. Unit 1 covers the Docker fundamentals, such as Docker Enterprise for Operations, Docker Enterprise for Developers, Swarm, and an introduction to Kubernetes. You will learn how to install Docker Community Edition, Docker Enterprise Edition with Kubernetes and CLI. Also, you will learn the Docker cycle, container lifecycle, develop applications in any language, wrap, build, ship, and deploy them for production. Finally, you will learn how to create a Swarm cluster, deploy an app to it, and manage it with the best practices according to the current technologies. Unit 2 provides quizzes to help you prepare for the certification test. The DCA exam format and the question style has changed since Mirantis acquired Docker. To accommodate this, the quizzes mirror these changes. You will: Understand the difference between containerization and virtualization Install Docker CE on various platforms and manage the resources Write Dockerfile, Docker Compose YAML, and Kubernetes manifest YAML files Compare microservices and monolithic applications Containerize monolithic applications.